Investigation of an electrolysis system with boron-doped diamond anode and gas diffusion cathode to remove water micropollutants. (26th November 2022) - Issa, Mohammad; Haupt, Dennis; Muddemann, Thorben; Kunz, Ulrich; Sievers, Michael
Abstract: Using electrolysis systems to degrade organics in wastewater encourages this technique to remove micropollutants (MPs) in different types of water. In this work, a cell consisting of an anode as a boron-doped diamond (BDD) electrode combined with a gas diffusion (GDE) cathode without a separator showed that MPs degradation can be effectively achieved. Investigating different operating parameters, it was stated that applying a low current density (2 mA/cm 2 ) and setting the Reynolds number of the electrolyte flow through the cell at the laminar range raised the treatment time by 3-fold at the same energy demand. This arrangement increased the MPs removal. Some substances like diclofenac were removed up to 84% at a longer treatment time of 180 min coupled with an increase in energy demand. The results at the mentioned parameters indicated an adequate generation rate of radicals needed to remove MPs and the oxidation reactions were promoted. The results show high potential to the investigated electrolysis system in removing MPs in wastewater under considering the need for further reduction of the energy demand. HIGHLIGHTS: Investigaton of innovative electrolysis system to remove water micropollutants. Explanation and controlling the system reactions towards the highest yield. Confirmation of removal possibility at different operating parameters. Studying how the operating parameters affect the treatment process effectivity. Determination of the best system settings to get the best removal efficiency. Graphical Abstract